Assembly of ligands interaction models for glutathione-S-transferases from Plasmodium falciparum, human and mouse using enzyme kinetics and molecular docking. (October 2016) - Al-Qattan, Mohammed Nooraldeen; Mordi, Mohd Nizam; Mansor, Sharif Mahsofi
Highlights: Binding modes and affinities for GST ligands were determined . Enzyme kinetic and docking studies were used in determination. GST isoforms studied include pfGST, hGSTP1, mGSTM1. Ligand–ligand interactions at P f GST binding sites were studied kinetically. The eligibility for given ligands as leads for GST inhibitors were discussed. Abstract: Background: Glutathione- s -transferases (GSTs) are enzymes that principally catalyze the conjugation of electrophilic compounds to the endogenous nucleophilic glutathione substrate, besides, they have other non-catalytic functions. The Plasmodium falciparum genome encodes a single isoform of GST ( Pf GST) which is involved in buffering the toxic heme, thus considered a potential anti-malarial target. In mammals several classes of GSTs are available, each of various isoforms. The human (human GST Pi-1 or hGSTP1) and mouse (murine GST Mu-1 or mGSTM1) GST isoforms control cellular apoptosis by interaction with signaling proteins, thus considered as potential anti-cancer targets. In the course of GSTs inhibitors development, the models of ligands interactions with GSTs are used to guide rational molecular modification. In the absence of X-ray crystallographic data, enzyme kinetics and molecular docking experiments can aid in addressing ligands binding modes to the enzymes. Methods: Kinetic studies were used to investigate the interactions between the three GSTs and each of glutathione, 1-chloro-2, 4-dinitrobenzene, cibacron blue, ethacrynic acid, S -hexyl glutathione, hemin and protoporphyrin IX. Since hemin displacement is intended for Pf GST inhibitors, the interactions between hemin and other ligands at Pf GST binding sites were studied kinetically. Computationally determined binding modes and energies were interlinked with the kinetic results to resolve enzymes-ligands interaction models at atomic level. Results: The results showed that hemin and cibacron blue have different binding modes in the three GSTs. Hemin has two binding sites (A and B) with two binding modes at site-A depending on presence of GSH. None of the ligands were able to compete hemin binding to Pf GST except ethacrynic acid. Besides bind differently in GSTs, the isolated anthraquinone moiety of cibacron blue is not maintaining sufficient interactions with GSTs to be used as a lead. Similarly, the ethacrynic acid uses water bridges to mediate interactions with GSTs and at least the conjugated form of EA is the true hemin inhibitor, thus EA may not be a suitable lead. Conclusions: Glutathione analogues with bulky substitution at thiol of cysteine moiety or at γ-amino group of γ-glutamine moiety may be the most suitable to provide GST inhibitors with hemin competition.